Study of basal < a > and pyramidal < c + a > slips in Mg-Y alloys using micro-pillar compression. Issue 11 (2nd June 2020) - Wu, Jing; Si, Shanshan; Takagi, Kosuke; Li, Tian; Mine, Yoji; Takashima, Kazuki; Chiu, Yu Lung
ABSTRACT: The effect of yttrium (Y) on the critical resolved shear stresses (CRSS) of < a > basal slip, 10 1 ¯ 2 ⟨ 1 ¯ 011 ⟩ tension twinning and < c + a > pyramidal slip has been studied using micro-pillar compression tests along selected orientations at room temperature, on two magnesium (Mg) alloys with different Y contents (0.4 and 4 wt.%). The CRSS of < a > basal slip increased slightly from 30 ± 1 MPa (for Mg-0.4Y) to 37 ± 3 MPa (for Mg-4Y). In Mg-0.4Y, the resolved shear stress to activate the 10 1 ¯ 2 ⟨ 1 ¯ 011 ⟩ tension twin was determined to be 45 ± 12 MPa, while in Mg-4Y it was 113 MPa. The compressed samples were studied using scanning electron microscopy (SEM), transmission Kikuchi diffraction (TKD) and transmission electron microscopy (TEM). It was found that < c + a > dislocations slip mainly on 1 ¯ 1 ¯ 22 (Pyra II) planes with a CRSS of about 119 MPa in Mg-0.4Y and slip mainly on 0 1 ¯ 11 (Pyra I) planes in Mg-4Y with a CRSS of 106 MPa. There is a significantly lowered CRSS ratio between < c + a > slip and < a > basal slip in both alloys (2.8 and 4.8) compared with that reported in bulk pure Mg (∼100). The easy activation of < c + a > on Pyramidal I slip is expected to promote the frequent cross-slip in Mg-4Y alloy.